2018
DOI: 10.1111/ped.13708
|View full text |Cite
|
Sign up to set email alerts
|

Lymphadenitis by non‐tuberculous mycobacteria in children

Abstract: Background Non‐tuberculous mycobacteria (NTM) constitute an important cause of cervical lymphadenitis in immunocompetent children. The aims of this study were to estimate the incidence of lymphadenitis due to NTM in children in Cyprus and to describe the characteristics, diagnostic approach, management and outcome of such infections. Methods Children aged 1–5 years old, evaluated at Archbishop Makarios III Hospital, Nicosia, Cyprus, from 1 January 2007 to 31 December 2016 for lymphadenopathy, were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…In population-based surveillance studies, estimates of the annual incidence of NTMs in children range widely from 0.8/100,000 children < 15 years in Australia to 3.1/100,000 children < 15 years or 11.3/100,000 children < 5 years in Germany and 0.8/100,000 children < 18 years in the Netherlands [14]. In children, NTM infection typically affects cervicofacial lymph nodes and manifests itself with an enlarged lymph node in the laterocervical region that appears as a painless lump that can spontaneously drain within weeks/months.…”
Section: Ntm Lymphadenitismentioning
confidence: 99%
See 1 more Smart Citation
“…In population-based surveillance studies, estimates of the annual incidence of NTMs in children range widely from 0.8/100,000 children < 15 years in Australia to 3.1/100,000 children < 15 years or 11.3/100,000 children < 5 years in Germany and 0.8/100,000 children < 18 years in the Netherlands [14]. In children, NTM infection typically affects cervicofacial lymph nodes and manifests itself with an enlarged lymph node in the laterocervical region that appears as a painless lump that can spontaneously drain within weeks/months.…”
Section: Ntm Lymphadenitismentioning
confidence: 99%
“…Surgery is the gold standard treatment for cervical lymphadenitis. Many authors have shown that surgery is effective, having an 81-100% cure rate with primary excision versus 45% for incision and drainage [1,13,14,16]. Then, the advantage of surgery is to allow histological and microbiological diagnosis.…”
Section: Surgical Therapymentioning
confidence: 99%
“…25 In a retrospective study by Loizos et al , 22 patients with confirmed NTM infections were treated with excisions. 26 However, in 12 cases, recurrences were observed. Five of these occurred in the first 2 months after surgery and required a second operation.…”
Section: Discussionmentioning
confidence: 99%
“…Ours is the 6th reported case of M. kansasii extrapulmonary lymphadenitis in immunocompetent adults; 5 cases in children under 18 have also been reported. (Table 1) [6], [7], [8], [9], [10], [11], [12], [13], [14]. Sites of dissemination included cervical and mediastinal lymph nodes, skin, brain, soft tissue, joint, and peritoneum.…”
Section: Discussionmentioning
confidence: 99%